Ottoman Traces in the Surroundings of Ohrid Lake (Macedonia) - (:unkn) unknown (MARMARA UNIV, 2015)
The Ottoman State, having ruled the Balkans more than five centuries, left behind a large number of historical and cultural monuments. Located in the southwest of Macedonia, the Ohrid Lake and its surroundings, with their natural beauty, as well as with their historical and cultural richness, constitute one of the sites with the highest touristic potential in the Balkans. The cities of Ohrid and Struga contain a lot of monumental structures belonging to the Ottoman culture and civilization, such as mosques, mausoleums, dervish lodges, prayer rooms, inns, baths, bazaars and markets. Residences conserving the traces of civil Ottoman-Turkish architecture still exist today. In Ohrid, among the mosques survived until nowadays and frequently visited by the tourists are to be mentioned those of Ali Pasha, Zeynelabidin Pasha, Emin Mahmud, Hadji Turgut, Hadji Hamza, Haydar Pasha and Kuloglu. In addition, at several churches and monasteries located in the center of Ohrid city can also be remarked the Ottoman traces. The Hagia Sophia Church and the Monastery of St. Clement constitute religious edifices that for a certain period were used by the Ottomans as mosques. The Mausoleum of Sinan Celebi and the Halveti Mehmet Hayati Lodge also belong to the Islamic edifices frequently visited in Ohrid, while a few kilometers away from Ohrid, near the St Naum Monastery, are to be found the remnants of Sari Saltuk Mausoleum. During the Ottoman rule in the Balkans, the lodges built with the mediation of Sufi murshids were very widespread among the Muslim population. Among these, the Halveti Hayati Hasan Baba Lodge represents a typical example of the 18th century Ottoman architecture.
Keywords: Ottoman Empire; City of Ohrid; monumental structures